Retention and mortality on antiretroviral therapy in sub-Saharan Africa: collaborative analyses of HIV treatment programmes - (:unkn) unknown (My University, 2018)
INTRODUCTION: By 2020, 90% of all people diagnosed with HIV should receive long-term combination antiretroviral therapy (ART). In sub-Saharan Africa, this target is threatened by loss to follow-up in ART programmes. The proportion of people retained on ART long-term cannot be easily determined, because individuals classified as lost to follow-up, may have self-transferred to another HIV treatment programme, or may have died. We describe retention on ART in sub-Saharan Africa, first based on observed data as recorded in the clinic databases, and second adjusted for undocumented deaths and self-transfers. METHODS: We analysed data from HIV-infected adults and children initiating ART between 2009 and 2014 at a sub-Saharan African HIV treatment programme participating in the International epidemiology Databases to Evaluate AIDS (IeDEA). We used the Kaplan-Meier method to calculate the cumulative incidence of retention on ART and the Aalen-Johansen method to calculate the cumulative incidences of death, loss to follow-up, and stopping ART. We used inverse probability weighting to adjust clinic data for undocumented mortality and self-transfer, based on estimates from a recent systematic review and meta-analysis. RESULTS: We included 505,634 patients: 12,848 (2.5%) from Central Africa, 109,233 (21.6%) from East Africa, 347,343 (68.7%) from Southern Africa and 36,210 (7.2%) from West Africa. In crude analyses of observed clinic data, 52.1% of patients were retained on ART, 41.8% were lost to follow-up and 6.0% had died 5 years after ART initiation. After accounting for undocumented deaths and self-transfers, we estimated that 66.6% of patients were retained on ART, 18.8% had stopped ART and 14.7% had died at 5 years. CONCLUSIONS: Improving long-term retention on ART will be crucial to attaining the 90% on ART target. Naive analyses of HIV cohort studies, which do not account for undocumented mortality and self-transfer of patients, may severely underestimate
Keywords: African Research